Dynamics of Urban Disaster Risk Paradigm: Looking Through the Perceived Lens of the Residents of Informal Settlements in Khulna City, Bangladesh. (March 2020) - Swapan, Mohammad Shahidul Hasan; Ashikuzzaman, Md; Iftekhar, Md Sayed
The integration of sustainability principles into disaster management research suggests a shift from traditional expert-driven assessment to a more community-driven process. However, most studies have focused on a generalized and regional assessment of perceived risk. Only a few of them have focused on informal settlements which belong to the most vulnerable communities facing the compound impacts of multiple disasters in urban areas. This raises concerns over the generalization of existing findings as informal settlements may add to spatial heterogeneity in disaster risk assessment. In order to contribute to this knowledge gap, we have surveyed 1, 122 households of 93 slums of Khulna city in Bangladesh. We have investigated informal settlers' perceptions of local and citywide hazard risks and their vulnerabilities from natural and anthropogenic hazards. It is found that low-income households are more concerned about the day-to-day inconvenience (e.g., waterlogging) rather than extreme weather events (e.g., cyclone and storm surge). This is mainly due to the degraded local environment and poor built form of their living places. The mapping of survey responses displays a spatial segregation of perceived disaster risk. The study highlights the importance of adopting spatial and risk-specific disaster preparedness policies and interventions. The results of the study would also be useful for tailoring appropriate disaster management policies to improve community resilience for poverty-stricken areas in developing countries.